Quality monitoring of microbial contamination of cryopreserved parathyroid tissue - Stotler, Brie A.; Reich-Slotky, Ronit; Schwartz, Joseph; Inabnet, William B.; Lee, James; Wu, Fann; Della-Latta, Phyllis; Jhang, Jeffrey S. (Cell and tissue banking, 2011)
Cryopreservation of parathyroid tissue (PT) provides patients undergoing parathyroidectomy with an option for delayed autologous heterotopic parathyroid transplantation. A standard protocol for quality monitoring of PT has not been established. This article describes a method for detecting the presence of bacterial contamination in PT tissue intended for autologous transplantation. PT was received in the tissue bank, processed under aseptic conditions, and placed into cryopreservation medium. Sterility testing was performed at 2 time points prior to cryopreservation. From January 2005 to October 2008, 47 PT samples were cryopreserved. The following bacteria were isolated from 11 PT specimens: Staphylococcus epidermidis , Staphylococcus capitis subspecies ureolyticus , Staphylococcus lugdunensis, Bacillus pumilus , and corynebacteria (diphtheroids) . 23% of PTs were contaminated at the time of collection, predominantly with indigenous bacteria. Quality monitoring using this protocol is a useful tool to identify tissues contaminated with bacteria.